2019
DOI: 10.3390/su11247043
|View full text |Cite
|
Sign up to set email alerts
|

SDGs and Innovation in the Business Context Literature Review

Abstract: On 25 October 2015 the United Nations approved The 2030 Agenda for Sustainable Development and its 17 sustainable development goals (SDGs). It is an important event from different points of view: clear judgment was expressed on the unsustainability of current development models, not only on the environmental level, but also on the economic and social ones. The implementation of the agenda requires a strong involvement of all members of society, especially business. The article aims to provide a literature over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 100 publications
0
35
0
1
Order By: Relevance
“…The adoption of ISO 56002‐2019 will embark the effect on triple bottom line or people, profit and planet (Kiatpanont, 2020), which will help the firm to contribute and fulfil the firm responsibility toward United Nation SDGs (Cordova & Celone, 2019; Lehoux et al, 2018) through adoption of green business operation and environmental standards. ISO 56002‐2019 will not only accomplish the environmental standards but also enhance the quality standards (Kiatpanont, 2020) which will contribute directly in achieving environmental SDG, economic SDG and indirectly in achieving social SDG for the societal development.…”
Section: Moderating Role Of Iso 56002‐2019 Innovation Management Systemmentioning
confidence: 99%
“…The adoption of ISO 56002‐2019 will embark the effect on triple bottom line or people, profit and planet (Kiatpanont, 2020), which will help the firm to contribute and fulfil the firm responsibility toward United Nation SDGs (Cordova & Celone, 2019; Lehoux et al, 2018) through adoption of green business operation and environmental standards. ISO 56002‐2019 will not only accomplish the environmental standards but also enhance the quality standards (Kiatpanont, 2020) which will contribute directly in achieving environmental SDG, economic SDG and indirectly in achieving social SDG for the societal development.…”
Section: Moderating Role Of Iso 56002‐2019 Innovation Management Systemmentioning
confidence: 99%
“…From this perspective, in novation involves the transformation of backbone systems of modern societies (e.g., energy, mobility, food, water, healthcare, communication) [35]. In the literature, we find references to the 3 Ds model [36], transformative innovation [28], responsible research and innovation [35], open innovation [2], social innovation [37], or challenge-or mission-oriented innovation [38].…”
Section: Two Keys For Implementation (Ii): Innovationmentioning
confidence: 99%
“…In the literature, we could find several business model innovations suitable for undertaking the transformations required by the 2030 Agenda at the level of firms [2]. Rath and Siebold [1], for example, talk about 'conscious enterprises' [68] as a suitable model to create shared value and generate transformational changes in firms.…”
Section: The Role Of the Private Sector: Responsible Innovation For Sustainable Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They argued that researchers should pay particular attention to understanding how and to what extent the SDGs can strengthen business strategy and performance measurement. Most notably, recent reviews of the literature have shown that the SDGs could be considered possible strategic drivers for business-related research due to the face of their value relevance [25][26][27]. Beyond business strategies, sustainable development requires innovative product design strategies in a variety of contexts to support social, economic, and environmental responsibility across the entire value chain.…”
Section: Introductionmentioning
confidence: 99%